EFEKTIVITAS SISTEM PENGENDALIAN INTERN PADA KINERJA INSTANSI PEMERINTAH DI DINAS PENDAPATAN DAERAH KABUPATEN MINAHASA UTARA - Sondakh, Renli Ferrari Daud; Saerang, David Paul Elia; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
In a government organization requires their internal control systems due to their system of internal control activities undertaken by government agencies more effective and avoid fraud and keep the business property of parties who are not responsible. The object of this research is the Dinas Pendapatan Daerah Kabupaten Minahasa Utara. The purpose of this study to analyze the effectiveness of the internal control system on the performance of government agencies in the Dinas Pendapatan Daerah Kabupaten Minahasa Utara. The method used is descriptive qualitative. The results showed that the internal control system used Dinas Pendapatan Daerah Kabupaten Minahasa Utara effective and sufficient for compliance with the Internal Control System of the Government that has been set by the government based on Government Regulation No. 60 of 2008, so that the achievement of revenue receipts and the realization of the region in 2015 is said to be very effective. Keywords: Government Accounting, Internal Control System of the Government, Performance, effectiveness, Dinas Pendapatan Daerah